Factor this expression completely, then place the factors in the proper location on the grid.
5x3 + 40y6

5x^3 + 40y^6 = 5(x^3 + 8y^6) = 5(x + 2y^2)(x^2 - 2xy^2 + 4y^4)

s

Question

Asked 11/18/2014 12:16:56 AM

Updated 11/18/2014 2:08:31 AM

1 Answer/Comment

Rating

8

5x^3 + 40y^6

= 5(x^3 + 8y^6)

= 5(x + 2y^2)(x^2 - 2xy^2 + 4y^4)

= 5(x^3 + 8y^6)

= 5(x + 2y^2)(x^2 - 2xy^2 + 4y^4)

Added 11/18/2014 2:08:31 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/18/2014 2:31:51 AM]

Factor this expression completely, then place the factors in the proper location on the grid.
x3y3 + z3

Question

Not Answered

Updated 11/18/2014 2:12:45 AM

1 Answer/Comment

Perform the indicated operation.
x3 x2
User: Perform the indicated operation.
(14x3y2z)4

Question

Updated 11/18/2014 2:05:47 AM

2 Answers/Comments

(14x^3y^2z)^4 = 38,416x^12y^8z^4

Added 11/18/2014 2:05:26 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/18/2014 2:32:52 AM]

Perform the indicated operation.
(3a2 - 7xy)(3a2 + 7xy)
**Weegy:** The answer is 9a^4-49x^2y^2. **User:** Perform the indicated operation.
(r + s)(r2 - rs + s2) **Weegy:** 3-3 = 0 **User:** Perform the indicated operation.
(2a2 - 8)(4a4 + 16a2 + 64)
**Weegy:** The answer for (2a2 - 8)(4a4 16a2 64) is 4096 a^6 (2 a^2-8). **User:** Factor this expression completely.
16x4 + 56x2 + 49
**Weegy:** 64, 112, 49 **User:** Factor this expression completely.
2x2 + 11x + 15
(More)

Question

Updated 11/18/2014 1:24:08 AM

5 Answers/Comments

(r + s)(r2 - rs + s2)

= r3 - r2s + rs2 + r2s - rs2 + s3

= r3 + s3

= r3 - r2s + rs2 + r2s - rs2 + s3

= r3 + s3

Added 11/18/2014 1:21:15 AM

This answer has been confirmed as correct and helpful.

2x2 + 11x + 15 = (2x + 5)(x + 3)

Added 11/18/2014 1:22:35 AM

This answer has been confirmed as correct and helpful.

16x^4 + 56x^2 + 49 = (4x^2+7)^2

Added 11/18/2014 1:23:36 AM

This answer has been confirmed as correct and helpful.

(2a2 - 8)(4a4 + 16a2 + 64) = 8a6 - 512

Added 11/18/2014 1:24:08 AM

This answer has been confirmed as correct and helpful.

Which are zeros of the following polynomial?
6x 2 - 11x - 10 = 0
x = 6, x = 10
x = ; x =
x = -2; x = 5
x = ; x =

Question

Updated 11/24/2014 12:49:26 AM

1 Answer/Comment

Which of the following polynomials has zeros at x = –4 and x = 7?
4x 2 - 7x - 11
4x 2 - 49
7x 2 - 4x + 28
x 2 - 3x - 28

Question

Updated 11/24/2014 12:47:32 AM

1 Answer/Comment

x^2 - 3x - 28 has zeros at x = –4 and x = 7.

x^2 - 3x - 28 = 0

(x - 7)(x + 4) = 0

x - 7 = 0 or x + 4 = 0

x = 7 or x = -4

x^2 - 3x - 28 = 0

(x - 7)(x + 4) = 0

x - 7 = 0 or x + 4 = 0

x = 7 or x = -4

Added 11/24/2014 12:47:32 AM

This answer has been confirmed as correct and helpful.

34,635,525

questions answered

There are no comments.